Pasteurella Canis as a Cause of Septic Arthritis and Soft Tissue Infection after Sheep Bite: A Case Report - Gálvez-Valdovinos Ramiro; Arellano Aguilar Gregorio; Gutiérrez-Velazco José Luis; Domínguez-Gasca Luis Gerardo; Domínguez-Carrillo Luis Gerardo (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2016)
Pasteurella spp is the first organisms to consider in any patient who presents with a soft tissue infection following cat or dog bites. Pasteurella canis is most common isolate of dog bites, but there are no reports of pastereulla canis infection caused by sheep bite. A case of a 66 years old farmer woman with symptoms of infected left hand with wrist septic arthritis, after a lamb bite is described (the sheep was sick after a dog bite). Microbiological examination of the wrist articular liquid was performed. The specimen was both aerobic and anaerobic cultures were performed. After 24 hours, growth of smooth, greyish-white colonies was observed only on Columbia agar. Another Gram stained slide was performed from those colonies and Gram negative cocobacilli to short rod shaped morphology with bipolar staining was observed. They demonstrate positive catalase and oxidase positive reaction. The bacterium was susceptible to all tested antimicrobial agents. Although systemic forms of Pasteurella are possible, cutaneous infections from animal bites are the most common presentation. Most animal-bite injuries can be treated with oral antimicrobials on an outpatient basis, but in this case the patient needed intravenous antimicrobial aggressive therapy.